Erlotinib or gefitinib for the treatment of relapsed platinum pretreated non-small cell lung cancer and ovarian cancer: a systematic review. - STORDAL, BRITTA KRISTINA (My University, 2011)
Background: Platinum-based chemotherapy is the standard of care for ovarian cancer and non-small cell lung cancer (NSCLC). However, resistance to platinum agents invariably develops. Targeted therapies, such as tyrosine kinase inhibitors (TKIs), have great potential here as they exert their anti-tumour effect via alternative mechanisms to platinum-based drugs and as such may remain unaffected by emergent resistance to platinum. Methods: A systematic review was conducted to investigate whether two EGFR-TKIs, erlotinib and gefitinib, have efficacy in the platinum-resistance setting. Preclinical studies of platinum-resistant cancer cell lines, which had been subsequently treated with EGFRTKIs,were sought to establish proof-of-concept. Clinical trials reporting administration of EGFR-TKIs to ovarian cancer and NSCLC patients relapsed after therapy with platinum drugs were investigated to determine sensitivity of these cohorts to EGFR-TKI treatment. The role of EGFR mutation, copy number and protein expression on response to EGFR-TKIs after failure of platinum chemotherapy were also investigated. Results: Preclinical models of platinum-resistant cancer were found which display a spectrum of cross-resistance profiles to EGFR-TKIs. Sensitivity to EGFR-TKIs is dependent on the activation of the EGFR pathway or EGFR interacting proteins such as HER-2. EGFR-TKIs show favourable response rates in platinum-pretreated NSCLC, 11.14% and 15.25% for 150 mg/day erlotinib and 250 mg/day gefitinib, respectively. These response rates significantly improve in patients of Asian descent (28.3% and 29.17%, respectively) and patients with EGFR activation mutations (41.6% and 63.89%, respectively) or increased copy number (33.3% and 45.45%, respectively). Gefitinib significantly outperformed erlotinib and should therefore be the EGFR-TKI of choice in platinum-pretreated relapsed NSCLC. In contrast, response rates are very poor to both erlotinib and gefitinib in platinum pretreated ovarian cancer, 0-5.9% and they should not be used in this cohort of patients. Preclinical models demonstrate that, while cross resistance can occur between platinums and EGFR-TKIs, there is not a generalised cross-resistance phenotype. Erlotinib and gefitinib are suitable for the treatment of platinum-pretreated NSCLC, particularly in patients with EGFR mutations or increases in copy number. Unfortunately, the high rates of EGFR protein overexpression in ovarian cancer are not translating to a clinically useful therapeutic target for EGFR-TKIs; EGFR mutations are rare in ovarian cancer. Newer TKIs may improve response rates in these cohorts and future clinical trials need to collect tumour biopsies from all patients to ensure the success of personalised chemotherapy.
PUBLISHED
Keywords: Cancer